Maize plant (Zea mays) uptake of organophosphorus and novel brominated flame retardants from hydroponic cultures. (January 2022) - Bonato, Tiziano; Beggio, Giovanni; Pivato, Alberto; Piazza, Rossano
Abstract: The root uptake and root-shoot translocation of seven organophosphorus flame retardants (OPFRs) and four novel brominated flame retardants (NBFRs) were assessed in this investigation using hydroponic grown maize plants ( Zea mays ). Three initial liquid concentrations for each considered compound were examined (i.e., 0.3 μg L −1, 3 μg L −1, 30 μg L −1 ). The results indicated that the 30 μg L −1 treatments were phytotoxic, as they resulted in a significant decrease in shoot dry weight. Plant-driven removal of the tested FRs decreased with the increasing initial spiking level and were reportedly higher for the NBFRs (range 42%–10%) than OPFRs (range 19%–7%). All the considered FRs were measured in the roots (range 0.020–6.123 μg g −1 dry weight -DW-) and shoots (range 0.012–1.364 μg g −1 DW) of the tested plants, confirming that there was uptake. Linear relationships were identified between the chemical concentrations in the plant parts and the tested hydroponic concentrations. Root concentration factors were positively correlated with the specific lipophilicity (i.e., log K ow ) of the tested FRs and were determined to be higher for the NBFRs than the OPFRs. The NBFRs had a higher root uptake rate than the OPFRs, and this trend was more significant with the increasing treatment concentrations. Shoot/root concentration factors were found to be lower than the unity value for 10 of the 11 tested compounds. These results can be related to the specific molecular configurations and the occurrence of different functional groups in the tested compounds. The results will help to improve risk assessment procedures and fine tune our understanding of human receptor responses to the ingestion of maize crops grown on agricultural sites irrigated with water contaminated by FRs. Graphical abstract: Image 1 Highlights: Root uptake occurred for all investigated FRs. Root uptake was linearly correlated with compounds lipophilicity. Higher concentrations were found in roots than in shoots for 10 out of 11 FRs. Functional groups of flame retardants can influence uptake and translocation.